Digest: Brain or brawn: Trade‐offs between brain size and flight mode in birds. (1st August 2022) - Saxena, Swati; Hosken, David J.; Dutta, Tusheema
Abstract: Brain size is extremely variable across species, and its evolution depends upon the calorific trade‐offs between it and other organs and activities. Shiomi investigated potential brain size trade‐offs with different flight modes in birds. Flight can be energetically expensive, and costs are especially high with powered flight. This comparative study indicated that migratory birds employing less energetic modes of flight had relatively larger brains than migratory birds using powered flight, suggesting that brain size is impacted by the energetic costs of flight.